Mana’s Funeral Stories : Function, Structure, and Constraints of One Woman’s Posthumous Stories - Gault, Cinda (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1996)
Noting that “everyday conversational narratives” are now being researched for what their structure and form can reveal about sociocultural patterns, the author recounts and analyzes a number of stories circulating in her own family about her late grandmother. She is alert to the dynamics of personal relationships, as well as to conventional notions about gender roles and social propriety, at work in the life of family tradition. Her interviews with relatives not long after her grandmother’s death demonstrate, she daims, that “funeral stories constitute a site for the negotiation of cultural and interpersonal meaning.”